Brain activity during pursuit and goal-conflict threat avoidance in major depressive disorder. (23rd August 2022) - Marwood, Lindsey; Wise, Toby; Kerr-Gaffney, Jess; Strawbridge, Rebecca; Williams, Steve C R; Cleare, Anthony J; Perkins, Adam
Abstract: Threat avoidance is a prominent symptom of affective disorders, yet its biological basis remains poorly understood. Here, we used a validated task, the Joystick Operated Runway Task (JORT), combined with fMRI, to explore whether abnormal function in neural circuits responsible for avoidance underlies these symptoms. Eighteen individuals with major depressive disorder (MDD) and 17 unaffected controls underwent the task, which involved using physical effort to avoid threatening stimuli, paired with mild electric shocks on certain trials. Activity during anticipation and avoidance of threats was explored and compared between groups. Anticipation of aversive stimuli was associated with significant activation in the dorsal anterior cingulate cortex, superior frontal gyrus, and striatum, while active avoidance of aversive stimuli was associated with activity in dorsal anterior cingulate cortex, insula, and prefrontal cortex. There were no significant group differences in neural activity or behavioral performance on the JORT; however, participants with depression reported more dread while being chased on the task. The JORT effectively identified neural systems involved in avoidance and anticipation of aversive stimuli. However, the absence of significant differences in behavioral performance and activation between depressed and non-depressed groups suggests that MDD is not associated with abnormal function in these networks. Future research should investigate the basis of passive avoidance in major depression. Further, the JORT should be explored in patients with anxiety disorders, where threat avoidance may be a more prominent characteristic of the disorder.